(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article describes the peculiarities of the economic situation in the Fergana Valley in 1917-1918, the establishment of the Soviet regime in the valley and the essence of the Bolshevik economic policy, the aggravation of the problem of food security in the valley, the mistakes of the Soviet authorities, the terrible famine in the Fergana Valley. the tragic landscape is analyzed on the basis of statistical collections, archival materials and scientific literature.